ANALISIS PERBANDINGAN RASIO PROFITABILITAS BANK (STUDI KASUS PADA PT. BANK PAN INDONESIA TBK. DAN PT. BANK PERMATA TBK. PERIODE TAHUN 2014-2021) - Ana Dwi Pertiwi (Asosiasi Dosen Muda Indonesia, 2023)
The economic level in developing countries can be seen from the market performance of banking institutions. Financial performance is a measure of management's level of success in operating the company's financial resources. Various methods including financial ratio analysis can be used to analyze a bank's financial performance. The profitability ratio is a ratio that is useful as a measure of a company's ability to generate earnings generated from sales. This study aims to analyze and compare the profitability ratios of Panin Bank and Permata Bank in 2014-2021 by using the Return On Assets (ROA), Return On Equity (ROE) and Operational Costs and Operating Income (BOPO) ratios. The research data is the annual report data of Panin Bank and Permata Bank in the period 2016 to 2021. The method in this study is a comparative method which aims to compare the profitability ratios of Panin Bank and Permata Bank in 2014-2021. The results of this study indicate that there are significant differences in the ROA and BOPO ratios of Panin Bank and Permata Bank and there is no significant difference in the ratio of ROE Panin Bank and Permata Bank